Floristic study of an ultramafic formation in Sitio Magarwak, Sta. Lourdes, Puerto Princesa City, Palawan Island, Philippines - Maria Ellenita; Jose Santos Carandang VI; Esperanza Maribel Agoo (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. De Castro ME, Carandang VI JS, Agoo EM. 2020. Floristic study of an ultramafic formation in Sitio Magarwak, Sta. Lourdes, Puerto Princesa City, Palawan Island, Philippines. Biodiversitas 21: 3769-3779. A study was done to assess the floristic composition of an ultramafic formation in Sitio Magarwak, Barangay Sta. Lourdes, Puerto Princesa City Palawan. A total of 52 trees and shrubs representing 30 families and 48 genera was recorded in the overstorey while the ground cover was dominated by 10 species mostly from families Poaceae and Zingiberaceae. The most dominant tree species include Dillenia monantha Merr., Xanthostemon speciosus Merr. and Schima wallichii ssp. oblata (Roxb.) Kurz. with Important Value Indices (IVIs) of 15.96%, 15.71%, and 14.20%, respectively. Level of endemicity was considerably high with 21 species classified as indigenous, 11 of which have their population restricted only on the island of Palawan. However, most of these endemics are now under threat based on the Updated List of Threatened Philippine Plants and their Categories (DAO No 2017-11) and the International Union for the Conservation of Nature (IUCN) Red List (2020-1). Two species are classified as ?critically endangered? (Olea palawanensis Kiew and Guioa palawanica Welzen) while the two are ‘endangered’ (Kibatalia stenopetala Merr. and Nepenthes philippinensis Macfarl.). Findings from this study suggest that appropriate conservation measures must be put in place to ensure protection of the native flora’s remaining population from further destruction.